Educational Tablets and their Effectiveness in Enhancing Teacher Engagement and Conceptual Understanding in History Instruction in Secondary Schools in Bagamoyo District, Tanzania - Prospery Mwansa Mwila (Action Research Journal Indonesia (ARJI), 2026)
Improving the quality of history instruction in secondary schools increasingly depends on the effective use of digital tools that enhance learner engagement and strengthen conceptual understanding. In Tanzania, educational tablets have been introduced in public secondary schools to support teaching and learning; however, their classroom application remains unclear, particularly regarding instructional practices and teacher preparedness in contexts such as Bagamoyo District. Although available, these devices are mainly used for supportive tasks, with limited evidence of meaningful pedagogical transformation in history education.This study assessed the effectiveness of educational tablets in enhancing teachers’ engagement and conceptual understanding in history instruction in public secondary schools in Bagamoyo District. It examined how tablets are used in lesson preparation and delivery. A convergent parallel mixed-methods design was adopted, integrating quantitative and qualitative approaches. The study involved 30 participants, comprising 20 history teachers and 10 academic teachers, selected through stratified random and purposive sampling techniques. Data were collected using structured questionnaires and semi-structured interviews. Validity and reliability were ensured through triangulation, pilot testing, and a Cronbach’s Alpha value of 0.72. Quantitative data were analyzed using descriptive statistics, while qualitative data were analyzed thematically using the constant comparative method supported by NVivo software. Findings indicate that tablets are strongly valued for lesson planning (80%) and digital exhibitions (64%), reflecting their usefulness in organizing and presenting instructional content. However, their integration into learner-centered strategies such as project-based learning remains limited (14%), with inconsistent use in historical timelines and classroom presentations. Challenges include inadequate pedagogical training, unclear policy direction, and insufficient technical support. The results correspond with the Technology Acceptance Model (TAM) and Technological Pedagogical Content Knowledge (TPACK), showing that although teachers recognize the usefulness of tablets, many lack the integrated competencies required for transformative instructional use.